A cross-sectional study to correlate oral hygiene habit among orthodontic patients with their clinical findings and periodontal treatment need - Maira Mansoor; Duaa Monis; Rameen Anjum; Tania Arshad Siddiqui; Hassam Anjum Mir; Rozina Nazir (BMC, 2024)
Abstract Background Orthodontic treatment requires good oral hygiene for successful completion of treatment. As protocol, patients are usually given instructions for oral hygiene and diet at the start of treatment, however, they are not fully followed. Different methods are employed in order to increase patient compliance including digital means, however, these are not possible in teaching hospitals with high burden of patient care and limited resources. The present study aims to correlate the patient reported behavior with their clinical findings and treatment need. This will enable us to identify potential sources of motivation which will be incorporated in daily practice and enable us to improve methods to enhance patient's behavior. Method A cross-sectional study was conducted in the orthodontic department of a semi-government teaching hospital from August to October 2023 using a modified questionnaire. The clinical examination was done using a Community Periodontal Index for Treatment Need-C (CPITN-C) probe. The diagnosis of presenting clinical conditions and treatment need was done using Community Periodontal Index for Treatment Need (CPITN) and Gingival Bleeding Index (BI). Data collected was analyzed for frequencies and correlation was done using Spearman Correlation Coefficient. P- value ≤ 0.05 was taken as statistically significant. Result The sample size consisted of 110 patients of which 60% were entitled to receive treatment. The predominant age group was 15-20 years (39.1%). Approximately 70% patients were in code 1 for CPITN and GI and in need of oral hygiene instructions. Overall patients' showed good level of awareness, however, they were not compliant in behavior. Conclusion Although patients showed a good level of awareness towards oral hygiene practices, there was a lack of compliance in following them. Patients were more concerned for being affected by dental caries due to poor oral hygiene than its effect on overall treatment outcome.